Karakteristik Penalaran Kuantitatif siswa dalam menyelesaikan Masalah Matematika ditinjau dari Jenjang sekolah - Yohanes Hariaman Nada (FKIP Universitas Mataram, 2023)
There are various types of thinking skills that can be developed by studying mathematics, one of which is the algebraic thinking skills. One of the abilities in algebraic thinking is quantitative reasoning ability. Quantitative reasoning ability is a fundamental ability for students to be successful in learning mathematics. However, the facts on the field show that there are still many students who have low mathematical reasoning abilities. The purpose of this study was to obtain an overview and characteristics of students' mathematical reasoning abilities, especially students' quantitative reasoning. This research uses a qualitative approach, while this type of research is a phenomenological study. Phenomenology is the study that describes what a person receives, feels and knows in his consciousness about the experiences he has experienced. The subjects of this study were students of class VI elementary school and class VII junior high school. Based on the results of the research and discussion, it can be concluded that there are similarities and differences in the characteristics of quantitative reasoning between students at the final level of elementary school and students at the initial level of junior high school.